(untitled) (Педагогіка вищої та середньої школи, 2022)
Forms, methods and receptions, are examined in the article, that take into account the features of design facilities in aesthetic education of junior schoolboys. The necessity of system their use is underlined in the process of aesthetic education students of initial classes